Lexicographic polynomials of graphs and their spectra - Cardoso, Domingos M. (2017)
For a (simple) graph $H$ and non-negative integers $c_0,c_1,…,c_d$ ($c_d ≠ 0$), $p(H)=\sum_{k=0}^d{c_k · H^k}$ is the lexicographic polynomial in $H$ of degree $d$, where the sum of two graphs is their join and $c_k · H^k$ is the join of $c_k$ copies of $H^k$. The graph $H^k$ is the $k$th power of $H$ with respect to the lexicographic product ($H^0 = K_1$). The spectrum (if $H$ is regular) and the Laplacian spectrum (in general case) of $p(H)$ are determined in terms of the spectrum of $H$ and~$c_k$'s. Constructions of infinite families of cospectral or integral graphs are also announced.